Temporal and Spatial Characteristics of Tidal Current in the Eastern Waters of Macao in Summer - FANG Shenguang; HUANG Chunhua; YU Fenghua; WANG Shijun; HE Yong (Renmin Zhujiang)
The eastern waters of Macao at the Pearl River Estuary are an important channel for water and sediment discharged by the west beach of Lingdingyang Estuary and Macao waterway.The measured data during the flood seasons shows that the waters feature semi-diurnal tidal currents,and the average velocity in this area is about 21~23 cm/s during the flood and 18~29 cm/s during the ebb.The flowing direction is stable,namely,N—NNW trending during the flood and S trending during the ebb,and tidal power is stronger in the south.The average velocity in the waters is mainly dependent on the tidal type,and the flood runoff mainly affects residual currents and tidal duration.A stagnant area is formed in the north of the waters during the flood,and the water and sediment in the south are transported outside the Lingdingyang Estuary.Wind on the sea surface has a significant impact on the vertical dynamic structure of flow in the range of 40% water depth,and residual flow direction in the range of 10% water depth near the sea surface has a good follow-up.During southwest wind,the maximum horizontal flow velocity gradient appears in the second flood and ebb stage and corresponds to the occurrence of the maximum sediment concentration in the tidal cycle.Due to the shallow water depth in the north of the waters,the bed shear gradient force is generally greater than that in the south.As a result,the sediment concentration observed in the north of the waters is significantly higher than that in the southeast.According to the comprehensive analysis,astronomical tides,flood runoff,and wind are the main controlling dynamic factors in the waters.The friction resistance of shallow water in the north is drastically larger than that in the south,which leads to a significant difference in tidal duration and phases of vertical floods and ebbs.As a consequence,the special vertical dynamic structure of convergence on the surface and dispersion at the bottom is formed in the waters,which is strengthened by massive freshwater runoffs during the flood seasons.This leads to the trend of surface diluted water drifting to the east and the invasion of the nearshore by bottom high-salt water.